Invasive pneumococcal disease among hospitalized children aged 28 days to 60 months in Jarkarta - Yuliarti, Klara; Hadinegoro, Sri Rezeki; Supriyatno, Bambang; Karuniawati, Anis (Southeast Asian journal of tropical medicine and public health, 2012)
Streptococcus pneumoniae is a leading cause of morbidity and mortality among children worldwide. Prevention of invasive pneumococcal disease (IPD) with a pneumococcal conjugate vaccine (PCV) is an effective approach to reduce the burden of pneumococcal disease. Nationwide epidemiological data is required prior to considering universal pneumococcal immunization for Indonesia. This preliminary study aimed to quantify the burden of IPD among hospitalized children at Cipto Mangunkusumo Hospital and Fatmawati Hospital, Jakarta. We studied 205 subjects aged 28 days to 60 months who were admitted with the diagnosis of pneumonia, meningitis, sepsis, and suspected occult bacteremia. Streptococcus pneumoniae was isolated from 1 of 205 blood specimens, giving an IPD proportion of 0.5%. The IPD case in this study was a 3-month-old baby with meningitis and bilateral lobar pneumonia. The Quellung test demonstrated serotype 7F. The isolate was susceptible to amoxicillin and Cotrimoxazole. Incidence of IPD could not be calculated due to low number of cases; this underscores the importance of surveillance of pneumococcal disease in Indonesia.